2006
DOI: 10.1177/0967010606073085
|View full text |Cite
|
Sign up to set email alerts
|

Critical Approaches to Security in Europe: A Networked Manifesto

Abstract: In the last decade, critical approaches have substantially reshaped the theoretical landscape of security studies in Europe. Yet, despite an impressive body of literature, there remains a fundamental disagreement as to what counts as critical in this context. Scholars are still arguing in terms of "schools" while there has been an increasing and sustained crossfertilization among critical approaches. Finally, the boundaries between critical and traditional approaches to security remain blurred. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(83 citation statements)
references
References 105 publications
1
70
0
12
Order By: Relevance
“…In a recent article, Browning and McDonald (2013) have suggested that the field of critical security studies in international relations largely revolves around three central themes (see also CASE Collective 2006;Peoples and Vaughan-Williams 2010). The first of these is an essential critique of traditional 'realist' approaches to security, whereby the referent object of security is the nation state, which exists in a system of competing self-interested state actors that live in an environment of anarchy -the Hobbesian 'war of all against all'.…”
Section: Disciplining Securitymentioning
confidence: 99%
“…In a recent article, Browning and McDonald (2013) have suggested that the field of critical security studies in international relations largely revolves around three central themes (see also CASE Collective 2006;Peoples and Vaughan-Williams 2010). The first of these is an essential critique of traditional 'realist' approaches to security, whereby the referent object of security is the nation state, which exists in a system of competing self-interested state actors that live in an environment of anarchy -the Hobbesian 'war of all against all'.…”
Section: Disciplining Securitymentioning
confidence: 99%
“…The question of what is being secured in the name of security has been a particular concern for scholars from the 'Aberystwyth School' of critical security studies concerned with human security (CASE Collective 2006;Booth 1991;Krause and Williams 1997), and for others for whom the normative implications of security and securitisation are paramount (see McDonald 2008). These scholars argue that the referent object of security should shift from national security and the state towards protecting individuals, or 'human security'.…”
Section: What Is Being Secured?mentioning
confidence: 99%
“…The chapters in this book have been influenced mainly by post-structuralism and constructivism, and particularly by the three "schools" of critical security studies, nicknamed by the places of their origin -Copenhagen, Paris, and Aberystwyth (C.A.S.E. Collective 2006;Waever 2004).…”
Section: What You See Is What You Get: the Broadening And Widening Ofmentioning
confidence: 99%